A natural resource-based view of climate change: Innovation challenges in the automobile industry. (15th December 2016) - Cristina De Stefano, M.; Montes-Sancho, María J.; Busch, Timo
Abstract: In recent years, uncertainty about climate change policies has deeply altered the competitive landscape of the automobile industry, and highlighted the key role that companies can play in reducing global CO2 emissions through technological innovation. Given the complexity of the innovation process in this industry, mainly due to an interactive relationship with the market, this study adopts a socio-technical transition perspective in order to understand the type of technological innovations that automobile companies have developed for reducing CO2 emissions from their products during a period of regulatory uncertainty. The Natural-Resource-Based View is used as a novel framework to categorize technological innovations into two important sets: product stewardship and clean technology. Product stewardship innovations are characterized by incremental changes in product components, with no substantial modifications of the core product concept. Clean technology innovations are characterized by significant alterations to existing product functionalities, infrastructure and consumer patterns, and imply major restructuring of both manufacturing processes and market acceptance. Under regulatory uncertainty, findings show that significant reductions of CO2 emissions from vehicles have been due to clean technology innovations. The benefits from clean technologies persist over time. In addition, complementarities between product stewardship and clean technology innovations have occurred, with positive effects on further CO2 emission reductions. These latter benefits, however, show only short-term effects, suggesting that continuous innovation in product stewardship is necessary in the next few years in this industry to survive in a carbon-constrained market. Highlights: Under uncertainty clean technologies are undertook to reduce carbon emissions. Interactions between product stewardship and clean technologies reduce CO2 . Continuous innovation in product stewardship is needed to reduce CO2 over time. Clean technologies innovations have long run effects on carbon emissions.